Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan PT. Nestle - Dharma, Budi; Siregar, Dedy Rahman (Jurnal Manajemen Akuntansi (JUMSI), 2022)
PT Nestle is a multinational food and beverage manufacturer headquartered in Vevey, Vaud, Switzerland. There are many products from the famous Nestle, including Nespresso, Kit Kat, Smarties, Nesquik, Stouffer's, Vittel and Maggi. Nestle has 447 factories, operates in 189 countries, and employs approximately 339,000 people. As a large company, of course Nestle of course has internal and external financial statements. In this case the company can use ratio analysis to the financial statements.This can be reflected in a report that describes the development of the company's financial performance in a certain period. These reports are commonly called financial statements. In order for financial statements to be meaningful to interested parties, it is necessary to conduct a relationship analysis of the items in the financial statements, which is often called Financial Statement Analysis. The purpose of this study, to determine how the financial performance of PT. Based on the analysis of profitability ratios, liquidity ratios, solvency ratios and the company has sufficient ability to take action in guaranteeing and paying off debts to creditors, and for the results of other business financial ratio analysis can be done. used as a benchmark for investors in investing funds into the company.